Reducing time to market in new product development - Eurenius, Erik; Teräväinen, Billy (My University, 2020)
Background New product development covers the entire process of bringing a new product to the market and is the main value adding activity for many of the companies who develop their own products. Achieving a short time-to-market for the process is a key driver in new product success and therefore product developers stand to benefit greatly in achieving a time-to-market reduction. Purpose The purpose is to examine contemporary research and in doing so, identifying best-practice principles, methods and tools to reduce time-to-market and thereby improve new product success. The findings will be the basis for an analysis for Husqvarna construction products’ current new product development efforts, to which the findings will be adapted and recommendations to achieve a reduced time-to-market will be compiled. Method A single case study approach was adopted of a qualitative nature and involved an extensive theoretical research and interviews with people involved in the new product development at Husqvarna Construction Products. The interviews were mainly held via video link, where notes were taken and later transcribed and compiled. A theoretical framework was produced, which in conjunction with the findings, served as a basis for the analysis and recommendations. Results The case study provided three distinct categories of challenges for Husqvarna Construction Products in achieving a reduced time-to-market, those related to prioritization and focusing of resources, frontloading, and quality-of-execution. What the findings showed was a general lack of resources that prevented properly fulfilling necessary front-end activities, with a lacking product specification as a result, which in turn impacts the quality-of-execution. Recommendations The final list recommendation includes reducing the number of simultaneous projects, stricter prioritization between projects, conducting prestudies to a higher degree, building more early prototypes, involving lead users and employing customer visit teams, standardization, evaluating the IT-structure, periodical co-location of two functions, restructuring of the production parts approval process, and a formalization of the knowledge management practices.
Keywords: new product development; time-to-market; TtM reduction; quality in NPD; lean product development; Husqvarna construction products; stage-gate